Analisis Penggunaan Hash Function dan Digital Signature pada Sistem Keamanan Informasi - Arya Bagas Saika; Muhammad Fauzul; Alif Akbar Rafsanjani; Rizky Hajriani Nasution; Marsha Ramadhani (JIKUM: Jurnal Ilmu Komputer, 2026)
Information security is a critical issue in the development of modern information systems due to increasing threats such as data manipulation, forgery, and unauthorized access. This study aims to analyze the use of hash functions and digital signatures as cryptographic mechanisms to ensure data integrity, authentication, and non-repudiation in information security systems. The research method used is a literature review by analyzing scientific journals related to the implementation of hash functions and digital signature algorithms in various information systems. The results show that hash functions play an important role in maintaining data integrity, while digital signatures provide assurance of authenticity and accountability of data transmission. The combination of hash functions and digital signatures is proven to significantly enhance the security of information systems and reduce the risk of data tampering and security breaches.